Non-contact temperature measurement at the Physikalisch-Technische Bundesanstalt (PTB). Issue 3 (27th May 2021) - Müller, I.; Adibekyan, A.; Anhalt, K.; Baltruschat, C.; Gutschwager, B.; König, S.; Kononogova, E.; Monte, C.; Reiniger, M.; Schiller, S.; Taubert, D. R.; Urban, D.; et al.
ABSTRACT: At the Physikalisch-Technische Bundesanstalt, the National Metrology Institute of the Federal Republic of Germany, the traceability of non-contact temperature measurement to the International Temperature Scale (ITS-90) is realised without gaps over a temperature range from −170°C to 3000°C. In this paper the main calibration facilities for the calibration of radiation thermometers at temperatures above 1000°C and measurement of spectral radiance, the calibration of radiation thermometers at temperatures below 1000°C, the calibration of infrared thermographic cameras together with a method developed at PTB to correct the non-uniform response of sensor arrays, the calibration of infrared hyperspectral imagers for remote sensing, and emissivity measurement for industry and remote sensing are described. These facilities are tailored for different temperature ranges and different spectral ranges to meet the demand of industry and research for precise, practical non-contact temperature measurement.